Analysis of mitochondrial proteomes and supercomplex structures in brain tissue - Brady, Laura (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2015)
Mitochondria play a complex multifactorial role in the control of cell bioenergetics. A primary function of mitochondria is the production of adenosine 5'-triphosphate (ATP) by the process of oxidative phosphorylation that takes place in the mitochondrial inner membrane and any malfunction of this metabolic cascade can severely affect the cell. Consequently, given the brains high-energy requirements, any decline in brain respiratory chain enzyme complexes activity could have a significant effect on brain function. Based on their cellular localization, mitochondria from brain can be divided into two major populations.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin